Coaching executivo: dinâmicas das relações entre o coachee, o coach e a organização - Pliopas, Ana Luísa Villares da Silva Vieira (2018)
Organizations have employed coaching to develop executives since the 1980s, and such practice has increased since then. Despite its wide use in organizations, there are few studies about the relationships established between the coachee, the coach and the organization, and such studies focus on the complexity of such relationships, in which there are multiple agendas of power games. Therefore, there is opportunity to deepen the understanding of triangular and dyadic relationships in executive coaching. This study is relevant as it deepens the understanding of a frequently employed organizational practice, but with few studies on the relationships between coachees, coaches and organization. The work is based on the social constructivist theoretical perspective, which aims to understand how people make sense of the world they live in and what they do, broadening, this way, the options for understanding a phenomenon. The methodological approach adopted was grounded theory, conducted in a manner consistent with social constructionism. Data were obtained with interviews of 45 people, being 16 coachees, 15 coaches and 14 professionals of Human Resources Administration. As result of the study, three main meanings on the dynamics of the relationships between the coachee, the coach and the organization were elaborated. Firstly, the triangular and dyadic relationships present in executive coaching were re-signified, suggesting that the relationships between the different actors in executive coaching have different dynamics and relevance. The relationship between the coach and the coachee is fundamental, and the maintenance of the confidentiality of the coaching sessions content, essential for preserving such relationship. Despite the importance of such relationship, the organization permeates the relationship between the coachee and the coach, since it is expected that coach and coachee will also comply with the interest of the organization. Another result elaborated from the study was a continuum, in which different coaching discourses were positioned. This continuum highlights a paradox present in executive coaching: the closer the coaching process is to the managerial discourse of coaching, prioritizing skills development to achieve organizational goals, the more coaching may assume an instrumental quality, subtracting the coachee’s relevance from the process. This has the potential to make the coaching process innocuous. Finally, a vertical dimension of executive coaching is proposed, which address topics that coaches and coachees go through during coaching sessions. This meaning offers an integrative perspective of coaching, in which different perspectives allow coachees to make meaning about their development.